Thoughts on Education in Hungary in the Age of Enlightenment (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2007)
Pedagogy, by gradually separating from philosophy, became an independent science at the age of enlightenment in Europe. The period of Hungarian Enlightenment was from the 70’s of the eighteenth century to the middle of the 1820’s. There had already been antecedents of the changes in Hungary, of course, in the earlier decades of the eighteenth century.